Guiding Foreign Policy of Russian Empire in Context of 1906 Fundamental Laws Creation - S. V. Kulikov (Научный диалог)
The article examines the process of solving the problem of managing the foreign policy of the Russian Empire when creating the Fundamental State Laws on April 23, 1906. It emphasizes the importance of retaining control over international relations by the monarch and the Ministry of Foreign Affairs, effectively removing it from the influence of the State Duma. The perspectives of the authors of three drafts of the Fundamental Laws — P.A. Kharitonov, A.P. Salomon, and Count A.F. Heyden — are presented. While Kharitonov and Salomon permitted the involvement of the State Duma in the conclusion of international treaties, Heyden excluded such participation. In January-February 1906, Kharitonov’s draft was revised by senior officials of the State Chancellery under the leadership of Baron Yu.A. Ikskul von Hildenbandt and Count D.M. Solsky. It is shown that in the Chancellery’s draft, both the emperor and the State Duma remained involved in the conclusion of international treaties. This draft was discussed in March 1906 in Count S. Yu. Witte’s cabinet, and in the Council of Ministers’ version, despite an expert review by Professor F. F. Martens, popular representation was stripped of its right to participate in international treaty-making. The necessity for this was also justified by a draft of the Fundamental Laws prepared by Professor O.O. Eichelman. Attention is given to the Special Conference chaired by Nicholas II in April 1906, which consolidated the monarch’s monopoly over foreign policy within the Fundamental Laws. Nevertheless, the author argues that these same Fundamental Laws indirectly ensured the influence of the State Duma in this area, as without its review and approval, the budget of the Ministry of Foreign Affairs and all related legislative proposals could not be submitted for the emperor’s endorsement.